The effect of uncertainty on investment - Kolev, Atanas,Randall, Timothy (European Investment Bank, 2024)
Using firm-level survey data combined with firm-level financial information, we investigate the effect of a subjective, firm-specific measure of uncertainty on firm investment and employment growth in the European Union. We find that uncertainty has an economically significant negative effect on investment. Uncertainty is found to have an economically significant negative effect on employment growth, as well. Firms perceiving uncertainty as a major investment impediment experience 1 p.p. lower employment growth compared to those that do not. Using our estimates, we find that non-financial corporate investment in the European Union in 2022 would have been higher by 1 p.p. of fixed assets, while employment growth would have been by 0.7 p.p. higher had uncertainty remained at its 2021 levels.
10.2867/723130
Keywords: Graue Literatur; Investition; Investitionsrisiko; Befragung; Erwerbstätigkeit; Nicht-finanzielle Kapitalgesellschaft; EU-Staaten; investment; corporate governance; corporate finance; economic growth; economic survey; job creation; economic activity; report